Artificial Intelligence Implementation Challenges in Newsrooms: A Concept Paper (The International Journal for Scientific Research, 2025)
Technological changes in journalistic practices occur continuously. Newsrooms in media organizations are keen to stay in line with the technological developments taking place around the world. Journalism suffers from successive technological revolutions, after websites, social media platforms, data journalism, and finally artificial intelligence. Artificial intelligence will be an integral part of the journalistic process soon. Many international media organizations have begun to introduce these technologies into newsrooms in order to benefit and develop journalistic practices. This article discusses the challenges to the use of artificial intelligence tools in newsrooms. The results showed four main challenges faced by journalists a decrease in creativity, job loss for journalists, limited technological skills, and ethical challenges with AI adoption. On the other hand, there are also challenges facing media institutions with AI adoption. They include financial struggles due to high costs, difficulty in dealing with big data, lack of technological infrastructure, and human resources. This study adds to ongoing literature and contributes to helping journalists and media organizations identify the most prominent challenges to adapting AI in newsrooms.
Keywords: Artificial Intelligence; Journalistic Practices; Newsrooms